2021
DOI: 10.2147/hiv.s333469
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitude, Behavior, and Socioeconomic Conditions of People Living with HIV in Indonesia During the COVID-19 Pandemic: A Cross-Sectional Study

Abstract: Purpose This study aimed to analyze the knowledge, attitude, and behavior of people living with HIV (PLWH) during the COVID-19 pandemic and the pandemic’s impact on their socioeconomic conditions, antiretroviral adherence, and worries. Materials and Methods This cross-sectional study was conducted in May–August 2020 at the Integrated HIV Center of Dr. Cipto Mangunkusumo General Hospital, Indonesia. The data were collected using an online questionnaire and an offline pap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 19 publications
1
10
1
Order By: Relevance
“…The studies carried out among PLHIV reported alterations in ART uptake as follows: a rate of 33.7%,less-than-excellent and 1.7% under-average adherence to antiretrovirals medications [ 22 ], an increase of 7% (from 5 to 12%) in the rate of non-adherence to HIV medications [ 23 ], a 23.1% decrease in obtaining antiretroviral medication[ 24 ], a rate of 8.2% one-dose-ART-medication miss and 13.2% ART uptake avoidance [ 25 ], 5% to 26% increase in the chance of ART supply failure [ 26 ], a 36% temporary non-adherence due to inadequate ART supply [ 27 ], a 13.25% rate of running out of ART medication during pandemic [ 28 ], a 27.4% rate of missing visits for the antiretroviral stock refill [ 29 ], a 3% decrease in ART uptake [ 30 ], a 24.0% rate of missing at least one dose of HIV medications [ 31 ], and a 3.6% of ART refill failure [ 21 ]. In addition, one study conducted among providers reported a 67.25% rate of ART-application-service suspension or postponement due to the COVID-19 pandemic [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The studies carried out among PLHIV reported alterations in ART uptake as follows: a rate of 33.7%,less-than-excellent and 1.7% under-average adherence to antiretrovirals medications [ 22 ], an increase of 7% (from 5 to 12%) in the rate of non-adherence to HIV medications [ 23 ], a 23.1% decrease in obtaining antiretroviral medication[ 24 ], a rate of 8.2% one-dose-ART-medication miss and 13.2% ART uptake avoidance [ 25 ], 5% to 26% increase in the chance of ART supply failure [ 26 ], a 36% temporary non-adherence due to inadequate ART supply [ 27 ], a 13.25% rate of running out of ART medication during pandemic [ 28 ], a 27.4% rate of missing visits for the antiretroviral stock refill [ 29 ], a 3% decrease in ART uptake [ 30 ], a 24.0% rate of missing at least one dose of HIV medications [ 31 ], and a 3.6% of ART refill failure [ 21 ]. In addition, one study conducted among providers reported a 67.25% rate of ART-application-service suspension or postponement due to the COVID-19 pandemic [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many patients had missed their HIV clinical visits, recovery support meetings, follow-up tests, and counseling services. The main causes of this general decline in clinical appointments were reported as follows: inadequate transport, police abuse, insufficient transportation funds to avoid exposure to COVID-19 [ 27 ], lockdowns [ 28 ], limited access to health services, reduced income, and inability to afford traveling to the health facility, being unable to get facemask, fear of COVID-19 [ 29 ], and fear of visiting hospitals [ 30 ]. Similarly, two studies conducted among healthcare providers reported disruptions in HIV services amid the pandemic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Indonesia, particularly during the COVID-19 pandemic, research on symptom experience and symptom management of the impact of ARV therapy on PWH has not been widely studied. During the COVID-19 pandemic in Indonesia, Karjadi et al (2021) performed a study on the knowledge, attitudes, and behavior of PWH, but did not particularly address symptoms or symptom management behavior. Previous research has exclusively focused on symptom management in cardiovascular, neurologic, and cancer patients (Voss, 2013).…”
Section: Introductionmentioning
confidence: 99%